Economic feasibility assessment of microgrids with renewable energy sources in Peruvian rural areas - Quispe Huarcaya, Juan Carlos (2023)
Electrifcation of Peru's rural areas is an issue of vital importance for economic growth. However, these areas still have poor quality electricity service or operate in a stand-alone mode with high cost of energy. To address this problem, one of the most promising strategies proposes the use of renewable energy technologies through the implementation of electrical microgrids (MGs). In this context, this research develops the analysis of 37 cases of rural villages throughout Peru in order to obtain the optimal MG design and the most feasible areas for its implementation, considering the associated costs, geographic location and load characteristics. For this purpose, an optimization process is carried out using HOMER Prosoftware with the aim of sizing the MG with the minimum net present cost and cost of energy. Then, an iterative process is developed in MATLAB software to map cost values, renewable contribution, emissions, the energy charge and the annual savings in the utility bill. This analysis considers fve scenarios base on a grid-connected MG (with sensitivity values of grid sellback price) and an of-grid MG system. The results show the geographic distribution of all the annual utility saving bill. For the grid-connected MG condition, it presents a proft in the range of $107.08 to $368.2 compared to loads connected to the grid; while for the of-grid MG condition, it presents a proft in the range of $1269 to $4976 in comparison with loads connected to a diesel generator.